Mecanismos de eficiência fotossintética envolvidos na tolerância ao excesso de amônio e luz em plantas de arroz - Martins, Francisco William Viana (2020)
Plants can obtain nitrogen from the soil in two main forms: nitrate and ammonium. In particular, the latter is predominant in flooded soils where low oxygenation allows its accumulation. However, several negative effects associated with the accumulation of ammonium in plants can occur, including from morphological changes to metabolic changes. To investigate how ammonium tolerant plants can protect its photochemical system, rice was exposed to sole ammonium (10 mM) or nitrate (10mM) supply as N-sources for up to eight days and exposed to high light (2000 µE) and moderate light (400 µE). Ammonium supplied plants did not exhibit any significant changes in PSII activity under moderate light, as compared to nitrate plants. Under both high NH4+ and light, rice plants exhibited a significant delay in dark PSII recovery (50%) only after the sixth day of exposure. In opposition, any significant change related to the accumulation of important photochemical proteins, such as PsbA, PsbE, PsbS, CP43 and LCA1 were observed in both ammonium and nitrate plants. In parallel, no significant evidence of oxidative stress in proteins localized in the thylakoidal fraction was observed in both N-sources. Interestingly, ammonium supplied plants displayed higher time-dependent light induction in NPQ associated with decrease in dark relaxation after the sixth day, which coincides with delay in dark PSII recovery. Subsequently, the BNPAGE analysis in thylakoids also revealed that ammonium-plants significantly accumulated higher amounts of free LHCII-CP24-CP29 and free LHC trimmers in high light. Taken together, our results suggest that high ammonium is able to induce delaying in PSII recovery, which is probably not dependent exclusively on photochemical proteins accumulation or oxidative damage on thylakoidal proteins. Otherwise, high ammonium combined with high light is able to trigger changes on the aggregation state of PSII antenna sub-complexes, which can affect directly NPQ and PSII activity. These processes may represent unusual photoprotective mechanisms that might be essential to preserve photosynthesis in rice plants grown under extreme environments of high ammonium and excess light where stomatal closure is frequent, which can contribute to aggravating the harmful energy balance in chloroplasts.